Increased Proliferation of the Ileal Epithelium as a Remote Effect of Ulcerative Colitis. Issue 10 (October 2016) - Sedghi, Shirin; Barreau, Frédérick; Morilla, Ian; Montcuquet, Nicolas; Cazals-Hatem, Dominique; Pedruzzi, Eric; Rannou, Emilie; Tréton, Xavier; Hugot, Jean-Pierre; Ogier-Denis, Eric; Daniel, Fanny
Abstract : Background: Aside from cases of backwash ileitis, the ileal mucosa of patients with ulcerative colitis (UC), an idiotypic inflammatory bowel disease, has received little attention despite the fact that colitis is known to trigger alterations in morphology and/or functions of the small intestine remotely. Methods: The ileal mucosa was studied in patients with UC and in a spontaneous model of colitis ( Il10/Nox1 dKO mice) mimicking the histological and clinical features of UC and was also studied in acute and chronic murine models of chemically induced colitis. Proliferation and apoptosis were assessed using morphological and immunohistological methods and Western blot analysis. Peyer's patch immune cell subsets were analyzed. Cytokines levels were quantified using quantitative PCR and Luminex xMAP technology. Total RNA from isolated ileal crypts was used for whole genome transcriptome analysis. Results: The most striking features were an increased ileal crypt length associated with an enhanced cell proliferation of the transit-amplifying cells along with activation of the Wnt/β-catenin and MAPkinase pathways. These changes did not result from intestinal inflammation as assessed by histology and/or pro-inflammatory cytokine expression levels. The increased proliferation rate was dependent on the duration but not on the severity of colitis and was observed in different mouse models of colitis, including the Il10/Nox1 dKO model and 2, 4, 6-trinitrobenzenesulfonic acid–treated mice. Interestingly, the ileal mucosa of patients with UC also displayed longer crypts and enhanced cell proliferation compared with control patients. Conclusions: These data show that despite the absence of inflammation in the small intestine, alterations in the ileal mucosa homeostasis are present in UC. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 6 September 2016.